CiteSpace-based Survey of International Advances in Chinese Traditional Culture Research in 1999-2019 - He, Wenjuan; Peng, Huimin; WE, Feifei (Pacific International Journal, 2024)
With the globalization strategy and the initiative “One Belt and One Road” in China, Chinese traditional culture has a great impact on the world. This study, based on CiteSpace, explores the total numbers, hotspots, characteristics and tendency of international research on Chinese traditional culture, by retrieving 866 articles from SSCI and A&HCI in the Web of Science (Core Collection). The results of the study revealed that: there is a strong increases in total output from 1999 to 2019 and the research on the theme of Chinese traditional culture has become interdisciplinary; the most productive authors aren’t the ones in the most cited documents and the journals on which the most cited documents publish aren’t the prolific journals; most of the researchers are from Hong Kong, Taiwan, mainland of China, Canada and USA. In view of the results, it is obvious that it is a good way to spread Chinese traditional culture over the world. It is strongly recommended that we should do more analysis on the international literatures with different paradigms, methods and metrics in order to get a more comprehensive and correct domain visualization map of Chinese traditional culture research.